Does Government Expenditure Reduce GDP Gap? Evidence from Bangladesh - Islam, M. Rafiqul; Hassan, A.F.M. Kamrul (Journal of Nepalese Business Studies, 2007)
In Keynesian macroeconomics fiscal policy plays the dominant role to steer the economy along its long run equilibrium path and also to cure the short run deviation from its long run level. Present paper examines this role of government expenditure, a tool of fiscal policy, in the context of the economy of Bangladesh. The paper employs cointegration and Error Correction Mechanism (ECM) to examine the short and long run relationship between economic growth and government expenditure. Findings of the study indicate that, in the short run, government expenditure does not play any statistically significant role in eliminating the gap between actual and potential output. However, a statistically significant cointegrating relationship is found between government expenditure and long run equilibrium output Journal of Nepalese Business Studies 2006/III/1 pp. 1-8